PERAN MODEL TEAM GAMES FOURNAMENT TERHADAP HASIL BELAJAR MATEMATIKA SD SISWA KELAS III SD - Sutriyani, Wulan; Novia, Shella; Sabila, Diah Erviani (Journal of Professional Elementary Education, 2024)
This study aims to determine the improvement of elementary mathematics learning outcomes after the implementation of the Teams Games Tournament (TGT) type of cooperative learning model for third grade students at SD Negeri 6 Ngabul Jepara. This research leads to the literature study method with interview, observation and documentation data collection techniques. The results showed that the application of the Teams Games Tournament (TGT) learning model was very influential in improving student learning outcomes, especially in mathematics in elementary school